Adalékok a hamburg-brémai egyháztartomány középkori bíráskodás-történetéhez - Balogh, Elemér (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
This study describes the jurisdiction of the Archbishop of Bremen. The northern region of the medieval ecclesiastical organization of the Sacrum Romanum Imperium began to be organized and integrated into the framework of European Latin Christianity in the 9th century. The first northern archdiocese was founded in Hamburg, which did not retain its central role for long in historical terms. The seat of the province was soon transferred to Bremen. In the current scarcity of local source material on ecclesiastical jurisdiction and relevant specialised literature, it is preferable to provide a summary of the general (ecclesiastical) historical wellsprings of canon law, the marginal conditions of church organisation and political history, and the developments in research. An exception is the Vogt Court (Vogtei), which represented and exercised the secular part of the jurisdiction of the Archbishop of Bremen, and whose institutional history is covered by a large body of sources and a rich literature.